Local ablative treatment with surgery and/or radiotherapy in single-site and oligometastatic carcinoma of unknown primary. (November 2021) - Pouyiourou, Maria; Wohlfromm, Timothy; Kraft, Bianca; Hielscher, Thomas; Stichel, Damian; von Deimling, Andreas; Delorme, Stefan; Endris, Volker; Neumann, Olaf; Stenzinger, Albrecht; Krämer, Alwin; Bochtler, Tilmann
Abstract: Background: Single-site carcinoma of unknown primary (CUP) is recognised as a distinct favourable subtype in the European Society of Medical Oncology (ESMO) classification. There is broad consensus that these patients are candidates for local ablative treatment strategies with surgery and/or radiotherapy, but data on their outcomes are scarce. Patients and methods: In this study, we have addressed the prospects of cure and prognostic factors in a retrospective cohort of 63 patients who were eligible for local treatment at our centre. Results: Median event-free (EFS) and overall survival (OS) were 15.6 months and 52.5 months, respectively. Of 61 patients who received local treatment, 20 (32.8%) remained event-free over a median follow-up of 28 months. Baseline clinical parameters including affected organ, number, volume and histology of metastases had no significant impact on prognosis, whereas deleterious  TP53  mutations and DNA copy number loss emerged as independent adverse risk factors with respect to EFS. Surgical treatment was associated with improved OS as compared to radiation-based therapy. Conclusion: Our study advocates to pursue localised treatment with surgery and/or radiotherapy whenever feasible and implies that genetic parameters might additionally determine the clinical course of single-site CUP patients. Graphical abstract: Image 1 Highlights: CUP patients amenable to local ablative therapy achieve long-term remission and cure. In CUP, candidates for local ablative therapy should be proactively identified. Single-site CUP patients frequently qualify for renewed local treatment at relapse. Deleterious  TP53  mutation and DNA copy number loss predict adverse prognosis in local CUP.